OS RISCOS DO DISCO: A valorização do objeto-disco na relação entre História e Música - Junior, Francisco Alcides cougo (Outros Tempos: Pesquisa em Foco - História, 2011)
This article proposes a new focus on the issue of using discs as historical sources. Based onthe concept of "practice of hearing, we conjecture about the possibility of analysis of material objectsfrom two perspectives: the collective and the individual. It is proposed also a theoretical discussionabout the relationship between history and music from specific sound formats.